2017
DOI: 10.1063/1.4979515
|View full text |Cite
|
Sign up to set email alerts
|

Interface formation during silica encapsulation of colloidal CdSe/CdS quantum dots observed by in situ Raman spectroscopy

Abstract: We investigate the encapsulation of CdSe/CdS quantum dots (QDs) in a silica shell by in situ Raman spectroscopy and find a distinct shift of the CdS Raman signal during the first hours of the synthesis. This shift does not depend on the final silica shell thickness but on the properties of the initial core-shell QD. We find a correlation between the Raman shift rate and the speed of the silica formation and attribute this to the changing configuration of the outermost layers of the QD shell, where an interface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…As the reaction progresses, the particles start to agglomerate, without significantly changing the nanocrystal size and distribution as observed in the UV-Vis absorption spectra (Figure 1). It was earlier demonstrated that the agglomeration rate is a strong function of the carbon chain length of the ligand, either because of the energetic barrier due to the interaction among the ligand monolayer or the repulsive potential between the two spheres, enhanced by the monolayer thickness of the ligands, as demonstrated by Biermann et al [41] Ligand exchange on the surface of the quantum dots was further investigated by thermogravimetric (TGA) and derivative thermogravimetric (DTG) analyses (Figure 3). Figure 3(a 3 Journal of Nanomaterials with the quantum dots through the carbonyl, such as OA [56][57][58].…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…As the reaction progresses, the particles start to agglomerate, without significantly changing the nanocrystal size and distribution as observed in the UV-Vis absorption spectra (Figure 1). It was earlier demonstrated that the agglomeration rate is a strong function of the carbon chain length of the ligand, either because of the energetic barrier due to the interaction among the ligand monolayer or the repulsive potential between the two spheres, enhanced by the monolayer thickness of the ligands, as demonstrated by Biermann et al [41] Ligand exchange on the surface of the quantum dots was further investigated by thermogravimetric (TGA) and derivative thermogravimetric (DTG) analyses (Figure 3). Figure 3(a 3 Journal of Nanomaterials with the quantum dots through the carbonyl, such as OA [56][57][58].…”
Section: Resultsmentioning
confidence: 91%
“…Among many cadmium chalcogenide semiconductors, CdSe quantum dots have been widely studied in the literature [38][39][40][41][42]. Cadmium chalcogenides are well-known for their synthesis, yields, reliability, and stability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The biocompatibility and the biomedical uses of QDs are highly dependent on their composition, which, besides containing heavy metals, also includes poorly biocompatible solvents employed in their synthesis [162,164,166,168,173]. This issue could be partially solved by coating QDs with a silica/MS layer able to displace the coordinated solvents while preserving [174] the QD core [175,176,177]. Unfortunately, the intrinsic toxicity associated with the forming elements and remainder solvents in their composition make them risky for in vivo biomedical applications.…”
Section: Inorganic-mesoporous Silica Nanocomposites Responsive To mentioning
confidence: 99%
“…26,27 During the encapsulation process, the organic ligands on the surface of the QDs are substituted for hydrolyzed silica monomers resulting in a tight interaction between the QD and the silica matrix. 28 Recently developed core-shell CdSe/CdS QDs have shown superior optical properties with particularly robust emission when encapsulated in silica, even in oxidative aqueous environments. 29 The silica matrix additionally provides a convenient platform for the versatile surface functionalization of these NPs with a large variety of organosilanes.…”
mentioning
confidence: 99%